2017
DOI: 10.1016/j.physa.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Room evacuation through two contiguous exits

Abstract: Current regulations demand that at least two exits should be available for a safe evacuation during a panic situation. Although the "faster is slower" effect is expected to take place near the exits, the evacuation time will improve because of the additional exits. However, rooms having contiguous doors not always reduce the leaving time as expected. We investigated the relation between the doors separation and the evacuation performance. We found that there exists a separation distance range that does not rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
8
27
0
2
Order By: Relevance
“…This is a well known phenomenon called the Faster-is-Slower effect. This effect was reported in numerical simulations [7,9] and it has also experimental support [43].…”
Section: Appendix a Testing Out Previous Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…This is a well known phenomenon called the Faster-is-Slower effect. This effect was reported in numerical simulations [7,9] and it has also experimental support [43].…”
Section: Appendix a Testing Out Previous Resultssupporting
confidence: 62%
“…The cutoff was set as R i + R j to assimilate the LAMMPS built-in function with the cluster definition given in Eq. (9). If a pedestrian has no neighbors within the cutoff distance, then it is a 1pedestrian cluster.…”
Section: Simulation Softwarementioning
confidence: 99%
“…A larger number of models have been proposed for agent-based crowd simulation. Many of these are based on the well-known and popular social forces model (SFM) by Helbing and Molnar (1995); for example, researchers have recently used this model directly to model evacuation scenarios (Sticco et al 2017) and with adaptations for specific situations (e.g. Li et al 2017).…”
Section: Simulation Modelmentioning
confidence: 99%
“…The tangential friction between pedestrians belonging to this blocking structure was shown to play a relevant role with respect to the whole evacuation delays [3,4]. However, either the amount of blocking structures or its time life can vary according to the door width, the presence of obstacles or fallen individuals [5,6]. Further * codorso@df.uba.ar studies on blocking structures appearing in granular media research can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%